A1.21 Inhibitory potential of specific acpas in two mouse subspecies genetically separated about one million years ago. (24th February 2016) - Grimm, C; Marklein, B; Jenning, M; Harre, U; Konthur, Z; Lehrach, H; Burmester, GR; Skriner, K
Abstract : Objective: Monoclonal Anti-citrullinated protein autoantibodies ACPA target different proteins and their role in RA is still largely unknown. We analysed the susceptibility of PWD Musmusculusmusculus subspecies, separated from Musmusculusdomesticus about one million years ago to collagen antibody-induced arthritis (CAIA) and the role of ACPA antibodies in the CAIA model of arthritis. Methods: CAIA was induced by administration of collagen antibodies followed by lipopolysaccharide injection. Two genetically distinct mouse strains, representatives of the subspecies Mus musculus domesticus and Mus musculus musculus were analysed for the development of clinical and histological signs of arthritis upon CAIA treatment. ACPA antibodies were tested by adding it to the CAIA cocktail. Autoantigenic profile was generated using protein macroarrays. Results: The wild-derived mouse strain PWD/Ph was highly susceptible to CAIA induced arthritis, whereas the classical laboratory strain C57BL/6J was resistant. Mice carrying chromosomes 5 or 12 from PWD on a B6 background display a B6-like phenotype in the CAIA model as well as the F1 hybrids (B6xPWD and PWDxB6) implicating the presence of dominant resistance modifiers in the C57BL/6J genetic background. The two mouse strains differ highly in their autoantigenic profile. Injecting specific monoclonal ACPAs reactive with the citrullintated H1 and H4 were able to block the CAIA induced arthritis. This inhibition can be explained in part by a Toll 9 dependent inhibition of osteoclasts. Moreover TLR2 activation via P.gingivalis LPS and lipomannan treated animals show a 80% reduction of arthritis score compared to E. coli LPS in a C57BL/6J CAIA model. Anti-collagen specific antibodies are increased in both strains B6 and PWD when arthritis is induced. Commercial CCP2 ELISA detected ACPA in animals regardless of the treatment. Using the arginine and citrulline containing peptides as control shows that this response is directed to the arginine containing peptide. Conclusions: The Mus musculus musculus derived mouse strain PWD/Ph is highly susceptible to arthritis development in the CAIA model. TLR2 activation blocks CAIA and specific ACPAs are able to block Osteoclast activation via TLR 9 activation and these monoclonal antibodies may be used as therapeutic antibodies in the future that protect from RA development.